• 2022-06-15
    曲线\( y = (x - 1){x^ { { 2 \over 3}}} \)的凹凸性,说法正确的是( ) .
    A: 在\( ( - {1 \over 5},0) \)内为凸,\( (0,{1 \over 5}) \)内为凹
    B: 在\( ( - {1 \over 5},0) \)内为凹,\( (0,{1 \over 5}) \)内为凸
    C: 在\( ( - \infty , - {1 \over 5}) \)内为凸,\( ( - {1 \over 5}, + \infty ) \)内为凹
    D: 在\( ( - \infty , - {1 \over 5}) \)内为凹,\( ( - {1 \over 5}, + \infty ) \)内为凸
  • C

    举一反三

    内容

    • 0

      求函数$y = {{1 + \root 3 \of {{x^2}} - \sqrt {2x} } \over {\sqrt x }}$的导数$y' = $( ) A: $ {1 \over 2}{x^{ - {3 \over 2}}} + {1 \over 6}{x^{ - {5 \over 6}}}$ B: $ - {1 \over 2}{x^{ - {3 \over 2}}} + {1 \over 6}{x^{ - {5 \over 6}}}$ C: ${1 \over 2}{x^{ - {3 \over 2}}} - {1 \over 6}{x^{ - {5 \over 6}}}$ D: ${1 \over 3}{x^{ - {3 \over 2}}} - {1 \over 6}{x^{ - {5 \over 6}}}$

    • 1

      函数\( y = x + \sqrt {1 - x} \)的极大值为( ) A: 0 B: 1 C: \( {5 \over 4} \) D: \( {4 \over 5} \)

    • 2

      将\(f(x) = {1 \over {1 + {x^2}}}\)展开成\(x\)的幂级数为( )。 A: \({1 \over {1 + {x^2}}} = \sum\limits_{n = 0}^\infty { { {( - 1)}^n}{x^{2n}}} \matrix{ {} & {} \cr } ( - \infty < x < + \infty )\) B: \({1 \over {1 + {x^2}}} = \sum\limits_{n = 0}^\infty { { {( - 1)}^n}{x^{2n}}} \matrix{ {} & {} \cr } ( - 1< x < 1)\) C: \({1 \over {1 + {x^2}}} = \sum\limits_{n = 0}^\infty { { {( - 1)}^n}{x^{2n}}} \matrix{ {} & {} \cr } ( - 1 < x < 1)\) D: \({1 \over {1 + {x^2}}} = \sum\limits_{n = 0}^\infty { { x^{2n}}} \matrix{ {} & {} \cr } ( - 1 < x < 1)\)

    • 3

      将函数\(f(x) = {e^x}\)展开成\(x\)的幂级数为( )。 A: \({e^x} = \sum\limits_{n = 0}^\infty { { { { x^n}} \over {n!}}} ( - \infty < x < + \infty )\) B: \({e^x} = \sum\limits_{n = 0}^\infty { { {( - 1)}^n} { { {x^n}} \over {n!}}} ( - \infty < x < + \infty )\) C: \({e^x} = \sum\limits_{n = 0}^\infty { { { { x^n}} \over {n!}}} ( - 1 < x < 1)\) D: \({e^x} = \sum\limits_{n = 0}^\infty { { {( - 1)}^n} { { {x^n}} \over {n!}}} ( - 1 < x < 1)\)

    • 4

      将\(f(x)=e^x\)展开成\((x-3)\)的幂级数为( )。 A: \(\sum\limits_{n = 0}^\infty { { { { {(x - 3)}^n}} \over {n!}}} \matrix{ {} & {} \cr } ( - 1, 1)\) B: \({e^3}\sum\limits_{n = 0}^\infty { { { { {(x - 3)}^n}} \over {n!}}} \matrix{ {} & {} \cr } ( - 1, 1)\) C: \(\sum\limits_{n = 0}^\infty { { { { {(x - 3)}^n}} \over {n!}}} \matrix{ {} & {} \cr } ( - \infty , + \infty )\) D: \({e^3}\sum\limits_{n = 0}^\infty { { { { {(x - 3)}^n}} \over {n!}}} \matrix{ {} & {} \cr } ( - \infty , + \infty )\)